Hypertrophic cardiomyopathy and hyperthyroidism: a report of three cases. Issue 6 (November 1974) - Symons, C.; Richardson, P. J.; Feizi, O.
Abstract : Symons, C., Richardson, P. J., and Feizi, O. (1974). Thorax, 29, 713-719. Hypertrophic cardiomyopathy and hyperthyroidism. The combination of hypertrophic cardiomyopathy and hyperthyroidism gives rise to a complex clinical picture as some of the symptoms and signs may be common to both conditions. The presentation and investigation of three patients are reported. In one patient there was evidence of progression from the hypertrophic obstructive phase to that associated with loss of outflow tract obstruction. The echocardiogram was especially useful in assessing the presence or absence of hypertrophic disease in the thyrotoxic subject. It is suggested that the long continued high-output circulatory state in clinically undetected hyperthyroidism may prove to be a stimulus for unrestrained cardiac muscle hypertrophy.